Perubahan Tradisi Baralek pada Masyakarat Minangkabau di Kecamatan Medan Denai Kota Medan - Era Syafriani; Neila Susanti; Muhammad Jailani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research aims to: describe changes in the baralek tradition in the Minangkabau community in Medan Denai District, Medan City, describe the factors causing the change in baralek in the Minangkabau Community in Medan Denai District, Medan City, describe the social actions of the community in implementing the baralek tradition in the Minangkabau community in Medan Denai District Medan City. This research uses a qualitative research method with a descriptive approach. The results obtained from this research are that the Minangkabau people in Medan Denai District continue to uphold Minangkabau cultural values, one of which is by continuing to carry out wedding procession procedures in accordance with Minangkabau customs. However, this was not fully carried out so that the baralek tradition underwent changes by adapting or modifying part of the procession in the baralek tradition. Factors causing changes in Minangkabau marriage procedures were; Economic Factors, Time Efficiency, Living Environment, Marriages of Different Tribes. The solidarity of the Minangkabau people remains strong. This can be seen from the contribution of the community working together in organizing a wedding party, such as working together in cooking and enlivening the event.